(untitled) (Journal of Applied Oral Science, 2011)
OBJECTIVE: The aim of this study was to investigate the effects of mineral trioxide aggregate (MTA), Sealapex, and a combination of Sealapex and MTA (Sealapex Plus) on the reaction of subcutaneous connective tissue of rats, and on cell viability and cytokine production in mouse fibroblasts. MATERIAL AND METHODS: The tissue reaction was carried out with dentin tubes containing the materials implanted in the dorsal connective tissue of rats. The histological analysis was performed after 7 and 30 days. Millipore culture plate inserts with polyethylene tubes filled with materials were placed into 24-well cell culture plates with mouse fibroblasts to evaluate the cell viability by MTT assay. ELISA assays were also performed after 24 h of exposure of the mouse fibroblasts to set material disks. RESULTS: Histopathologic examination showed Von Kossa-positive granules that were birefringent to polarized light for all the studied materials at the tube openings. No material inhibited the cell viability in the in vitro test. It was detected IL-6 production in all root-end filling materials. MTA and Sealapex Plus induced a slight raise of mean levels of IL-1β. CONCLUSIONS: The results suggest that Sealapex Plus is biocompatible and stimulates the mineralization of the tissue.